(untitled) (Salam International Academic Journal, 2012)
This article defines the political rights of women in general terms. At first, the words polities and political rights have been detined. Then, the writer has posed the question whether the term political rights is correct or it is better to replace it with the term political obligations. The forms of the political rights (obligations) have been described and arguments have been made from Sharia for the participation of women. Enjoining the good and forbidding the evil, as well as advice have also been discussed. The writer has argued that enjoining good includes all aspects of life and the political arena is not only one but also an important part of it, and this not only implies obligation for man, but also for woman. The author further argues that pledge of allegiance is a political activity and obligation and both male and female have obligation in this regard. Shura, the importance of shura in political arena and participation of women in shura have been discussed in the article. Later in the article. Jihad and Hijra have been discussed and argument has been made that both Jihad and Hijra are a political activity and women have fully participated in it during the early Islamic era. Collective duties, among them, the political rights/obligations have been discussed and collective obligations have been identified in political arena. At the end of this paper the writer has defined and discussed capricious usage of right and negative capriciousness re right. The writer have also referred to some political stanees of women during the early Islamic era Wrapping up the article, the writer has made a number of conclusions and have made some recommendations regarding political rights/obligations of women.